High-Level swimmers` kinetic efficiency during the underwater phase of a grab start - Elipot, M.; Dietrich, G.; Hellard, P.; Houel, N. (Journal of Applied Biomechanics, 2010)
The purpose of the present work was to study swimmers` efficiency during the underwater phase of the grab start. Eight high-level swimmers participated in this study. They performed two types of start: a regular grab start (with underwater leg propulsion after the glide) and a grab start with no underwater movement (swimmers had to remain in a streamlined position). Four cameras filmed the entire underwater phase of all starts. Nine anatomic landmarks were identified on the swimmers` bodies and their positions were calculated using a modified double plan DLT technique. From these positions and Dempster`s anthropometric data, the center of mass position and velocity were also determined. Kinetic energies were also calculated. This velocity and kinetic energies for the two types of start were compared. Swimmers began underwater leg propulsion 1.69 m too soon. The global and internal energies were significantly higher for the start with underwater leg propulsion. Nevertheless, swimmers` velocities were equivalent for both starts. These results suggest that the swimmers did not use the underwater phase of the start efficiently: By kicking too soon, they did not succeed in producing higher velocities and thus wasted energy.